(untitled) (Perner’s Contacts, 2018)
The paper presents a mathematical model of tactical conflict prediction of a pair of aircraft. The objective of a tactical conflict prediction is to signal immediate danger situation to an air traffic controller. The conflict volume of en aircraft L is in the airspace formed around the aircraft L that is fixed in the centre of the conflict volume which is a rotational ellipsoid. The aircraft M moves with a constant relative velocity R with regard to aircraft L. If the extrapolated trajectory has at least one common point with the protected volume , then the point is enclosed in the protected volume and the conflict is signalled.